BREAKING BARRIERS: THE CONTRIBUTION OF WOMEN LEADERS TO FINANCIAL PERFORMANCE IN LOCAL GOVERNMENTS - Fahmiati Fahmiati; Victoria K. Priyambodo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Women are still underrepresented in public sector leadership, despite their significant numbers in the workforce. Previous research suggests that women leaders bring innovation, effective communication, and transformational leadership, which can improve financial performance. However, research results are still inconsistent. This study examines the impact of female leadership and demographic factors such as age, education, and tenure,on the financial performance of local governments in Indonesia. Using Upper Echelons Theory as a framework, this study provides empirical evidence to understand the role of gender in public sector financial performance. Methods: This research is a quantitative study using multiple linear regression to examine the impact of gender, age, tenure, and education level of regional leaders on local government financial performance. The analysis was conducted using STATA software to obtain accurate and efficient results. The study focuses on regional governments in Java Island, with purposive sampling based on leadership tenure (2020–2022) and availability of audited LKPD by the Audit Board of Indonesia (BPK RI). Results: Regression results show that education level positively affects profit margin (coef. = 0.0136; p = 0.008), while age is significantly associated with better debt management (NDTR; coef. = 0.0062; p = 0.046). Longer tenure improves debt-to-asset ratio, rate coverage, and asset turnover, but reduces tax revenue share, indicating shifts in fiscal strategy. Gender has no significant impact, suggesting that structural and institutional factors outweigh demographic characteristics in influencing financial performance. Conclusion and suggestion: This research examines how the characteristics of regional leaders influence the financial performance of local governments. in Java Island during 2020–2022. The results indicate that gender does not significantly affect financial performance. However, regional leaders' age, tenure, and education level significantly influence various aspects of financial management, such as debt management, asset utilization, and profit margins. These findings support Upper Echelons Theory, which emphasizes the role of demographic characteristics in leadership effectiveness. This study has limitations, including its focus exclusively on Java. Future research should extend to other regions to provide a more comprehensive perspective. Moreover, upcoming research should incorporate institutional factors such as governance quality and fiscal transparency, which may influence financial performance. Keywords: Financial Performance, Upper Echelons Theory, Women Leaders